Pola Adaptasi Petani dalam Pengelolaan Lahan Pertanian - Kirana Triasputri; Erwin Erwin; Lucky Zamzami (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this study was to determine the adaptation pattern of farmers in managing agricultural land. This study uses a qualitative approach method with a choice of case study methods. The results of this study indicate that because of the Nagari Ketaping farming community's land being made for the construction of the airport, they made several changes such as changes from a cultural to socio-economic perspective. Most of them can read business opportunities and can take advantage of this phenomenon well, but of course there are some unscrupulous people who take advantage of this phenomenon in bad ways, such as violating the norms that have developed in society. All these actions are based on the rational attitude of farmers in thinking. The farmers want a decent life and want to get ahead, but the problem so far is they don't have access to the market. The conclusion of the research is that the Minangkabau International Airport provides several good benefits for the community. although at first the affected farmers experienced confusion in managing agricultural land after the construction of the Minangkabau International Airport, slowly the farming community began to be able to find adaptation patterns so that they could continue to survive and earn a decent income. Keywords: Adaptation Patterns, Farmers, Land Management, Social Change